Advancing age and ischemia elevate the electric threshold to elicit spreading depolarization in the cerebral cortex of young adult rats. Issue 5 (May 2017) - Hertelendy, Péter; Menyhárt, Ákos; Makra, Péter; Süle, Zoltán; Kiss, Tamás; Tóth, Gergely; Ivánkovits-Kiss, Orsolya; Bari, Ferenc; Farkas, Eszter
Spreading depolarizations of long cumulative duration have been implicated in lesion development and progression in patients with stroke and traumatic brain injury. Spreading depolarizations evolve less likely in the aged brain, but it remains to be determined at what age the susceptibility to spreading depolarizations starts to decline, especially in ischemia. Spreading depolarizations were triggered by epidural electric stimulation prior and after ischemia induction in the cortex of 7–30 weeks old anesthetized rats ( n  = 38). Cerebral ischemia was achieved by occlusion of both common carotid arteries. Spreading depolarization occurrence was confirmed by the acquisition of DC potential and electrocorticogram. Cerebral blood flow variations were recorded by laser-Doppler flowmetry. Dendritic spine density in the cortex was determined in Golgi-COX stained sections. Spreading depolarization initiation required increasingly greater electric charge with older age, a potential outcome of consolidation of cortical connections, indicated by altered dendritic spine distribution. The threshold of spreading depolarization elicitation increased with ischemia in all age groups, which may be caused by tissue acidosis and increased K + conductance, among other factors. In conclusion, the brain appears to be the most susceptible to spreading depolarizations at adolescent age; therefore, spreading depolarizations may occur in young patients of ischemic or traumatic brain injury at the highest probability.